Attention, Interpretation, Memory (AIM) and Family Resilience as Flourishing Determinants in Early Adult - Tessalonika Sembiring; O.Irene Prameswari Edwina; Jeans Esparanci (Analitika: Jurnal Magister Psikologi UMA, 2023)
This study aims to see whether there is a mechanism for the role of AIM (Attention, Interpretation, Memory) on flourishing with family resilience factors as mediators. Respondents in this study were 241 early adult individuals (aged 20-40 years). Data were collected using a researcher-modified family  resilience questionnaire from the Walsh Family resilience Questionnaire (WFRQ). AIM questionnaire consisting of negative thinking  and positive thinking. The flourishing questionnaire  used was the Mental Health Continuum Short Form (MHC-SF; Keyes 2005, in Hone 2014). The collected data were analyzed using Model 4 of SPSS PROCESS mediation analysis (Hayes, 2018). The results showed that AIM (attention, interpretation, and memory) in the form  of both positive  thinking and negative thinking provides a direct role in the flourishing  of early adult individuals. Positive  thinking has a greater direct effect on  flourishing than negative thinking on flourishing  . Meanwhile,  family resilience  does not mediate the role of AIM (Positive thinking  and negative thinking) on family resilience.